Experience of test tasks severity analysis: some school mathematics problems severity - Krylovas, Aleksandras; Kastickaitė, Joana (Lietuvos matematikos rinkinys, 2013)
In this article, authors describe applied mathematical of students’ knowledge testing methodology using closed tests with the parallel performance of question’s options for many years. By presenting test tasks with severity experience of analysis, examining some of the challenges of school mathematics.